Performance evaluation and load demand management of grid connected hybrid wind-solar-battery system - K. M. Venkatachalam; V. Saravanan (Institute of Advanced Engineering and Science, 2020)
In this paper, Performance of the grid connected hybrid wind-solar energy system and load demand response of the battery integrated single phase voltage source inverter is presented. The wind energy conversion system is generating AC power and the solar PV system is generating DC power and both are integrating with battery in the common DC bus. The output voltage of the wind and solar system are controlling using dc-dc converters and it achieved more than the battery voltage. P&O algorithm used MPPT based voltage controller is driving the dc-dc converter with a reference voltage value of the battery. The single-phase full-bridge converter is converting DC to AC power and feeding into the standalone AC loads and distribution grid with IEEE 519 standard. The bi-directional converter is controlling the directions of power flow and it operates two modes namely inverter mode and rectifier mode based on a voltage level of the battery. In this bi-directional converter is controlling by the PI controller with the reference value of the DC bus voltage and load current. The power quality and demandresponse of the inverter is observing at various types of load conditions in standalone mode and grid-connected mode using experimental results.